ANALISIS SWOT TRANSFORMASI DIGITAL PADA LANSIA DALAM PENGGUNAAN JASA PERBANKAN DI INDONESIA ERA SOCIETY 5.0 - Muhammad, Alfian (Jihbiz: Global Journal of Islamic Banking and Finance, 2023)
The purpose of this study is to answer the problems that occur in the elderly in the use of banking services in Indonesia in the era of society 5.0 by using a SWOT Analysis. This research is a type of library research using a qualitative descriptive approach. After conducting a SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis regarding digital transformation in the elderly in using banking services in Indonesia in the era of society 5.0, it can be concluded that the development of technology in financial institutions has a high level of effectiveness to provide quality banking services to the elderly, but the level of use is still low, because many elderly people do not understand how to use digital services  Banking. Preferably, banking companies provide chatbots services for the elderly who want to do digital banking transactions. If an elderly person wants to make transactions using digital banking services, then it can start a conversation with chatbots and all their complaints will be resolved and replied to automatically, although it is unlikely that chatbots will do so to replace banking employees.